Не рычите на собаку! : книга о дрессировке людей, животных и самого себя - Прайор Карен (Плюс одна победа, 2011)
Экземпляры: (20120516) / Инвентарный номер: 47616 / Цена: 232.27 / Сис.шифр: 88.53 47616 / Авт.знак: П 68 / ББК: 88.53